The relationship of daily income, marital status, nutritional status and anemia with work-related fatigue among wanita tukang suun in the heritage area of Badung Market post the COVID-19 pandemic - Dewi, Putu Ratna Suprima; Noviyanti, Ni Putu Ayu Wulan; Putra, I Kadek Agus Dwija (Universitas Gadjah Mada, 2024)
Purpose: The COVID-19 pandemic has affected all aspects of life. The socio-economic aspect is one of the affected aspects. This study aimed to determine the relationship between income, marital status, nutritional status, and anemia status with work fatigue among wanita tukang suun at the Badung Market Heritage area after the COVID-19 pandemic. Methods: The type of research used in this research is observational analytic with a cross-sectional research design. This research was conducted in the Badung Market Heritage area. The sample of this study was taken by total sampling and obtained 107 respondents. The exclusion criteria in this study were wanita tukang suun who were under 18 years of age and had jobs other than as wanita tukang suun. The data in this study were collected using several instruments. Results: Wanita tukang suun mostly earns more than IDR 50.000 per day with a total of 75 respondents (70,1%), is married with a total of 96 respondents (89,7%), has a normal BMI with a total of 56 respondents (52.3%), have mild anemia with a total of 92 respondents (86.0%), experience light fatigue with a total of 92 respondents (86.0%). Conclusion: The results of this study indicate that there is a relationship between anemia status and nutritional status with work fatigue. Variables of daily income and marital status are not related to the incidence of work burnout among wanita tukang suun.